2014
DOI: 10.3389/fpls.2014.00695
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sulfate restriction on seed yield and quality of winter oilseed rape depends on the ability to remobilize sulfate from vegetative tissues to reproductive organs

Abstract: Our current knowledge about sulfur (S) management by winter oilseed rape to satisfy the S demand of developing seeds is still scarce, particularly in relation to S restriction. Our goals were to determine the physiological processes related to S use efficiency that led to maintain the seed yield and quality when S limitation occurred at the bolting or early flowering stages. To address these questions, a pulse-chase 34SO2−4 labeling method was carried out in order to study the S fluxes from uptake and remobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Sulphur application increased the availability of other major nutrients N, P and K [5] and enhanced sesame growth under drought conditions [6]. Its deficiency negatively affects the crop growth phases, crop maturity [8,9] and oil quality of oilseed crops [10,11]. Moreover, application of low S or S free fertilizers has decreased the S inputs to agriculture fields during the last 20 years [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulphur application increased the availability of other major nutrients N, P and K [5] and enhanced sesame growth under drought conditions [6]. Its deficiency negatively affects the crop growth phases, crop maturity [8,9] and oil quality of oilseed crops [10,11]. Moreover, application of low S or S free fertilizers has decreased the S inputs to agriculture fields during the last 20 years [12].…”
Section: Introductionmentioning
confidence: 99%
“…The higher seed yield production has increased the rate of sulphur removal from soil [6,13]. Oilseed crops need more S than cereal crops because it promotes pod initiation, whereas a deficiency of S aborts pods [10]. Overall, an optimum amount of S application considerably enhances the sesame growth [2] and seed quality by increasing the oleic acid content in oilseeds [11].…”
Section: Introductionmentioning
confidence: 99%
“…Oilseed rape (Brassica napus L.), one of the three major oil crops in the world, provides edible oil and raw materials for bio-energy production (Karp and Richter 2011;Girondé et al 2014). As one of the most important commercial and agricultural crops, oilseed rape is sensitive to Mo deficiency in soil, which affects its growth, production and seed quality.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [3][4][5][6] believe that the demand for rapeseed for sulphur (S) and boron (B) is large and amounts to 20 to 30 kg S·ha −1 [7], while for boron it amounts to 145 to 290 g·ha −1 [8]. Zhao et al [9] reported that sulphur and boron are necessary for the synthesis of glucosinolates and sulphur amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur is absorbed by the roots in the form of sulphate ion SO 4 2-and transported via xyl to the leaves. The sulphate ion is reduced in the leaves mainly to cysteine and/or transformed into methionine or incorporated into proteins [7,10]. According to Wielebski [11], the most important functions of sulphur in a plant result from the presence of this component in sulphur amino acids (cystine, cysteine, and methionine), which participate in the formation of proteins, and are also precursors of other important compounds, such as glucosinolates, glutathione, thiamine (vitamin B1), biotin (vitamin H), coenzyme A, lipoic acid, thioredoxins, and sulpholipids.…”
Section: Introductionmentioning
confidence: 99%